2018
DOI: 10.1186/s12894-018-0360-5
|View full text |Cite
|
Sign up to set email alerts
|

Obesity impairs male fertility through long-term effects on spermatogenesis

Abstract: ObjectiveThis study aimed to investigate the effect and possible underlying mechanisms of high-fat diet-induced obesity on spermatogenesis in male rats.MethodsA total of 45 male rats were randomly divided into control (n = 15, normal diet) and obesity groups (n = 30, high-fat diet) and were fed for 16 weeks. Body weight and organ indexes were determined after sacrifice. Indicators of reproductive function, including sperm count, sperm motility, apoptosis of spermatogenic cells, and oxidative stress levels, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
43
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 39 publications
9
43
0
9
Order By: Relevance
“…9 Vacuolar alterations in seminiferous tubules, spermatogenic cell dysfunction, and increased apoptosis of spermatogenic cells in testicular tissue was also observed in HFD treated rats. 23 Currently, many herbal medicines therapeutic available been recommended for the treatment of obesity. Eurycoma longifolia Jack (EL) or Tongkat Ali is a very well-known traditional medicine, EL has gained remarkable consideration in latest years because of its beneficial effects for many disorders and diseases and its strong sexual enhancing effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Vacuolar alterations in seminiferous tubules, spermatogenic cell dysfunction, and increased apoptosis of spermatogenic cells in testicular tissue was also observed in HFD treated rats. 23 Currently, many herbal medicines therapeutic available been recommended for the treatment of obesity. Eurycoma longifolia Jack (EL) or Tongkat Ali is a very well-known traditional medicine, EL has gained remarkable consideration in latest years because of its beneficial effects for many disorders and diseases and its strong sexual enhancing effects.…”
Section: Discussionmentioning
confidence: 99%
“…A former study has proposed mechanisms that EL has the capability to activate the steroid 17 α monooxygenase to promote the metabolism of pregnenolone and 17 hydroxy pregnenolone to yield more dehydroepiandrosterone (DHEA), 4-androstenedione, and eventually to produce testosterone. 26,23 Other investigators showed that the presence of the specific inhibitors for the cytochrome P450scc (CYP11a),17,20-lyase,17β-hydroxy-steroid-dehydrogenase(CYP17a) and calcium ion channel such as aminoglutethimide, ketoconazole and the calcium ion channel blocker, nifedipine, significantly influenced the testosterone levels. 27 EL root extract was outstanding and successful in the management of male infertility in.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant enzymes include superoxide dismutase (SOD), catalase (CAT), and glutathione S-transferase (GST). A recent study in an obese mouse model showed decreased SOD in the testicular tissues of obese rats [53].…”
Section: Effects Of Obesity On Sperm Dna Integritymentioning
confidence: 96%
“…The experience of male infertility is still a major public health problem represents a negative psychological burden, health costs and ostracism and social discrimination in some contexts with a strong emphasis on child-bearing. While there has been extensive focus on the female infertility, the growing body of literature suggests an correlation between male infertility and some other chronic disorders, ranging from cardiometabolic, oncologic and autoimmune disorders to increased mortality rate later in life [5][6][7][8][9]. The exact underlying pathophysiology of these associations remains unclear, although it is suggested that genetic, intrauterine environment and lifestyle factors may play a role [8,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%